A New Device for Intraoperative Renal Blood Flow Measurement During Open‐Heart Surgery: An Experimental Study and the Clinical Pilot Study. Issue 10 (2nd May 2013) - Tirilomis, Theodor; Popov, Aron F.; Hanekop, Gunnar G.; Braeuer, Anselm; Quintel, Michael; Schoendube, Friedrich A.; Friedrich, Martin G.
Abstract Renal blood flow (RBF) may vary during cardiopulmonary bypass and low flow may cause insufficient blood supply of the kidney triggering renal failure postoperatively. Still, a valid intraoperative method of continuous RBF measurement is not available. A new catheter combining thermodilution and intravascular Doppler was developed, first calibrated in an in vitro model, and the catheter specific constant was determined. Then, application of the device was evaluated in a pilot study in an adult cardiovascular population. The data of the clinical pilot study revealed high correlation between the flow velocities detected by intravascular Doppler and the RBF measured by thermodilution (Pearson's correlation range: 0.78 to 0.97). In conclusion, the RBF can be measured excellently in real time using the new catheter, even under cardiopulmonary bypass.